Social neuroscience: how we learn to avoid the bully: dispatches - Maier, Eduard; Grinevich, Valéry (Current biology, 2024)
During social interactions, individuals evaluate relationships with their peers and switch from approach to avoidance, particularly in response to aggressive encounters. A new study in mice investigated the underlying brain mechanisms and identified oxytocin as a key regulator of social avoidance learning.